Дослідження поселення Маріамполіс у 2009 р. - Баранов, В.І.; Бобровський, Т.А.; Карлов, С.В. (Археологічні дослідження в Україні, 2010)
The first season of research of mediaeval settlement Mariampolis (Bakhchisaray) is described. The Early Mediaeval structure of possibly manufacturing function with a big cob stove was partially researched and a large set of artifacts of the Mediaeval Age was collected.